Communication - Buffa, Elwood S.; Scriabin, Michael; Vergin, Roger C. (Management Science, 1976)
(1) “On a Paper by Scriabin and Vergin” by Elwood S. Buffa, Graduate School of Management, University of California, Los Angeles. (Comments on Scriabin, M., R. C. Vergin. 1975. Comparison of computer algorithms and visual based methods for plant layout. Management Sci. 22 (2) 172–181) (2) “Computer and Visual Methods for Plant Layout—A Rejoinder” by Michael Scriabin and Roger C. Vergin, Faculty of Management Sciences, Simon Fraser University, Burnaby, British Columbia, Canada. (Comments about details of Scriabin, M., R. C. Vergin. 1975. Comparison of computer algorithms and visual based methods for plant layout. Management Sci. 22 (2) 172–181 where Buffa [Scriabin, M., R. C. Vergin. 1976. Computer and visual methods for plant layout—a rejoinder. Management Sci. 23 (1) 104] felt were defects in research design)